The Impact Of The Integration Of Performance Evaluation - Elfertas, Zoulikha Hanane (جامعة الوادي University of Eloued, 2025)
In this research, we tried to address the problem of how the integration of the two training and performance evaluation processes contributes to the development of human resources in the organization, and through our research, we touched on the definition of human resources development in addition to the role of the effectiveness of the performance evaluation and training process in the development of the human resource. On this basis, we have divided the research into the following elements: -The first axis: a conceptual introduction to human resources development -The second axis: the effectiveness of the performance evaluation and training process in the development of the human resource Through this study we have been able to reach the following main results: - Human Resources Development is intended to help employees meet the challenges created by technological developments and other types of development in the work environment, in addition to developing their skills and behaviors to serve the goals of the organization. - The process of performance evaluation is the process of comparing the results of performance measurement with the previously defined criteria. The training process is defined as the process of learning new knowledge, methods and behaviors that lead to the achievement of the organization's goals. - The human resources function in the organization is concerned with the training process because it is of great importance on the performance of the worker or human resource, through which the human resource is provided with a set of skills, behaviors and knowledge to achieve the goals of the organization.Without forgetting that the evaluation process is a necessary process and periodically to check the success of the training process in addition to identifying the training needs of the human resource.
The impact of the integration of performance evaluation and training on Human Resources Development
Keywords: human resource-training-performance; evaluation-training; program-competencies